If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + 7) = 24 Reorder the terms: 3(7 + y) = 24 (7 * 3 + y * 3) = 24 (21 + 3y) = 24 Solving 21 + 3y = 24 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + 3y = 24 + -21 Combine like terms: 21 + -21 = 0 0 + 3y = 24 + -21 3y = 24 + -21 Combine like terms: 24 + -21 = 3 3y = 3 Divide each side by '3'. y = 1 Simplifying y = 1
| 2y-14=x | | -2(-2x-3)=(-2) | | -6B=-420 | | 6a-9=50 | | -8+a=27 | | 4u-12=56 | | 12=-x+9-5x | | 5x-6+x^2=2 | | 9t^2=3t | | (2w-1)(2w-1)x^2=21 | | -4n-2=3n+5 | | 9j+4=4j+14 | | 5/7ab-35b | | 3x-6=15x+18 | | 4y+5=y+9 | | 0.5x+10=1.8x+25.6 | | (4m+1)(m+11)=0 | | m-1/6-4m+5/6= | | ln10/9 | | 162x^4y^2+32y^2= | | x(x)+6x=7 | | (9x-8)(5x+9)= | | 5/8y+7/8y+1/8y= | | 1134=6(x+16) | | x(x)-12x=-8 | | 4m+7(3m-8)= | | (2+x)(x)(3)=240 | | -.3p-2.1=-3.6 | | 3x(x)+14x-5=0 | | (4200*2/3)6 | | -2x+7(0)=11 | | 2x+4=2x+3(-1x+2) |